1994
DOI: 10.1159/000475262
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Lithotripsy Monotherapy for Staghorn Calculi

Abstract: maximum length on plain X-rays were treated by extracorporeal shock wave lithotripsy (ESWL) monotherapy for a period of 2 years. Thirty patients, with a follow-up of more than 6 months after the last treatment, were included in this study. The surface area of the calculi was 1,290 mm^2 on average. Based on plain X-rays, 9 cases (30%) became free of calculi while 12 patients (40%) had a small amount of residual fragments (less than 100 mm2 in area). Adding these cases to those in which all the residual calculi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…For renal calculi of <400 mm2 (600 renal units) the success rate was 87%, and for upper ureteral stones (175 renal units) 85%. These results strongly corroborate the results of some other authors [5,7,12,13].…”
Section: Eswl On Solitary Kidneysupporting
confidence: 93%
See 2 more Smart Citations
“…For renal calculi of <400 mm2 (600 renal units) the success rate was 87%, and for upper ureteral stones (175 renal units) 85%. These results strongly corroborate the results of some other authors [5,7,12,13].…”
Section: Eswl On Solitary Kidneysupporting
confidence: 93%
“…More than 90% of the stones can be disintegrated and 70% completely eliminated 3 months after lithotripsy [4], Yet, for large, especially staghorn stones, the combined approach (percutaneous nephroli tholapaxy and ESWL) is generally recommended. Nev ertheless, some lithotripsy centers have also reported quite good results with ESWL monotherapy [5][6][7][8][9][10], Ob viously, ESWL monotherapy treatment of staghorn stones, even in patients with 2 good functioning kidneys, brings substantial risk of complications, first of all frag ment obstruction. In solitary kidney stones, especially staghorn stones, the risk of obstruction and consecutive anuria could be one more reason for this treatment com bination.…”
Section: Eswl On Solitary Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…Di Silverio et al [10] suggested that SWL monotherapy should be recommended in patients with no dilatation of renal pelvis or calyces. Some authors also reported that the efficacy of treatment has more to do with the size of the pelvis and calyces, as well as the diameter of the ureteropelvic junction than with the size of the calculi [3,11,12]. It seems that there is much controversy regarding the factors predicting the outcome of SWL monotherapy for the management of staghorn calculi.…”
Section: Discussionmentioning
confidence: 99%